The Potential of Using Gold Dinar for International Trade Among OIC Countries - Irma Naddiya, Mushaddik (2013)
This purpose of this research was to study the possible introduction of Gold Dinar into Organization of Islamic (OIC) countries and to examine the implications of using the Gold Dinar, especially with the respect to international trade. The present study, casts light, through investigating the current usage of Gold Dinar in international trade, on the pros and cons of using Gold Dinar, and emphasizes its strengths. This research, aims to examine interest in using the Gold Dinar as well as to outline the obstacles to expanding its use. Moreover, there is also a focus on using the Gold Dinar as a payment settlement method for international trade. To achieve the objectives of this research, qualitative research methods including content analysis and interviews were used. The study utilized personal interviews with scholars, and studying books, journals, magazines, as well as the empirical analysis from the available evidence such as documents published by the IMF, UN and OIC. The study found that establishing a Gold Dinar trade bloc would encourage intra-trade among OIC members. This effect would be more robust than those generated by the currently existing economic blocs within the OIC countries. Obstacles to implementing the Gold Dinar among OIC countries included political, social, and cultural factors. However, the main obstacle was a lack of understanding and the application of the Islamic Shari’ah. Malaysia’s proposal that Muslim countries use the Gold Dinar is a serious, practical idea if Islamic countries would implement it. Adopting the Gold Dinar amongst OIC countries with an Islamic fiscal policy an Islamic monetary system would lead to the amendment of international monetary relations in the direction of creating a stable and just global monetary system. The implementation of Gold Dinar would solve the problems inflation, change the value of money and bring stability to our financial obligations and transactions.